Identity signalling in shields: how coastal hunter-gatherers use rock art and material culture in arid and temperate Australia. Issue 2 (3rd May 2016) - McDonald, Jo; Harper, Sam
Abstract: This paper explores inter-group signalling behaviour of hunter-fisher-gatherers living in arid and temperate coastal regions in Holocene Australia. We examine shield designs in the rock art of two visually similar engraved art provinces on opposite sides of the Australian continent: Port Hedland and Sydney. We explore the question of inter-group social signalling behaviour in arid versus fertile environments by testing the stylistic heterogeneity of shield designs in both art provinces. We examine the stylistic diversity of historically-collected and illustrated shields from both regions, and compare these with the engraved repertoires of the two style provinces. One of the precepts of information exchange theory (IET) is that publicly-displayed items/artefacts will provide the best vehicles for projecting cultural identity information. We assume that shields, as items of material culture which are carried publically, would have been ideally suited to signal individual, local and broader group identity. In more fertile areas it is usually argued that hunter-gatherers demonstrate increased territoriality and social boundedness as a result of demographic packing and focused resources, compared to groups in arid areas where there are widely ramified social networks. We test the hypothesis that a greater degree of stylistic heterogeneity should be displayed by engraved Sydney shields compared with those found in Port Hedland. However, our analyses demonstrate the reverse of this prediction. We suggest some alternative explanations for how style has been used in the arid coastal Pilbara, and suggest refinement is needed of some expectations in information exchange theory in arid zones where there is focalised resource availability and extreme language hybridity.